Monoclonal Antibodies against Small Molecule Natural Products and Their Applications, Eastern Blotting and Knockout Extract - Yukihiro Shoyama (MDPI AG, 2011)
To determine the hapten number in hapten-carrier protein conjugate matrix-assisted laser desorption/ionization (MALDI) tof mass spectrometry was applied. Highly specific anti-ginsenoside Rb1 and Rg1 monoclonal antibodies (MAbs) were prepared. Ginsenosides were developed on thin layer chromatography (TLC) plates which were covered by a polyvinylidene difluoride (PVDF) membrane resulting in blotting. The membrane was treated with NaIO4 solution to release the aldehyde group on the sugar moiety of the ginsenosides. By treatment of the membrane with a protein solution the ginsenoside-protein conjugation as a Schiff-base occurred, which can function to fix it to the PVDF membrane. A part of the ginsenoside aglycone was reacted with anti-ginsenoside Rb1 MAb, secondary MAb conjugated with enzyme and finally a substrate was added, resulting in a specific and highly sensitive staining that we named Eastern blotting. Furthermore, it makes one-step isolation of ginsenoside Rb1 possible using an immuno-affinity column conjugated with anti-ginsenoside Rb1 MAb. Furthermore, immunoaffinity concentration was carried out allowing high sensitivity analysis of lower concentrations of ginsenoside Rb1 so that several unknown bands could be structurally determined.